Study on Directional Control Curtain Grouting Technology in Boulder-Cobble Strata - HAN Yu; YANG Jian; CAO Chunding (Renmin Zhujiang)
The boulder-cobble strata has the characteristic of stranger permeability along the downstream direction of the river,but the impervious curtain perpendicular to the river is difficult to form.In order to solve this problem,the grouting pipe based on embedded flower pipe technology is reformed by directional mechanical transformation.The limited energy emitted by the slurry from the pulse grouting pump is used to make the slurry penetrate along the square direction of vertical seepage,and the direction is controllable,and the grouting material and process flow are optimized.The two indexes of certain pressure and single stage suction are taken as the grouting end standard,the problems that traditional grouting method of large-size stratum such as boulder-cobble stratuml is difficult to start pressure,the cement consumption is large,and the slurry permeability path usually extends to the upstream and downstream of the river are effectively solved.The grouting test shows that the directional curtain grouting technology has good applicability to the large particle size floating gravel stratum.After the directional control grouting treatment,the water permeability is greatly reduced,which meets the anti-seepage requirements of medium and low dam foundation;it has reference significance for similar projects.